National Ag-Data Hub project technical report - phase one - Beyene, Melkamu; Yilma, Daniel; Mohammed, Aminu; Kebede, Fikru; Tibebe, Degefie; Tamene, Lulseged D. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This document is a technical progress report of a work aimed to develop a national ag data hub in Ethiopia. The document is not a full technical implementation report of the national ag data hub. It is the technical report of the first phase as per the agreement entered between CIAT and ACATECH TECHNOLOGY PLC to implement the system in a phase by phase approach. This report has two main parts. The first part provides background information about the project which includes a brief introduction about the first phase deliverables. This shows the scope of the project to be completed in the first phase (i.e. in the last three months). The second part describes the project activities and progress in contrast to the plan set at the beginning. This part clearly showed the progress achieved so far.